Advances in Multimedia Information Processing - PCM 2014 15th Pacific Rim Conference on Multimedia, Kuching, Malaysia, December 1-4, 2014, Proceedings - Ooi, Wei Tsang; Snoek, Cees G.M; Tan, Hung Khoon; Ho, Chin Kuan; Huet, Benoit; Ngo, Chong-Wah (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2014)
This book constitutes the refereed proceedings of the 15th Pacific Rim Conference on Multimedia, PCM 2014, held in Kuching, Malaysia, in December 2014. The 35 revised full papers and 6 short papers presented were carefully reviewed and selected from 84 submissions. The papers cover a wide range of topics in the area of multimedia content analysis, multimedia signal processing and communications, and multimedia applications and services. They have been organized into topical sections on video coding, annotation, image and photo, applications, people, image analysis and processing under extra help, nearest neighbor, neural networks, and audio. Also included are sections with best papers and posters and demonstrations.